STRATEGI GURU DALAM MENINGKATKAN EFEKTIFITAS PROSES PEMBELAJARAN PADA MATA PELAJARAN SEJARAH KELAS X IPS DI MAN 1 MALANG - Astuti, Erfa Ila Fuji (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
The importance of teachers’ strategy in the learning process is inseparable from the occurrence of several obstacles faced by the students. It is especially related to History subject. This subject is well-known for its numerous theories and stories. Thus, to make the teaching and learning process effective and to prevent boredom during the class activity, the teachers must apply the suitable strategies in teaching, particularly for history subject. The writer has formulated the objectives of this study, namely: (1) to describe the strategies which is usually use in the history of learning process (2) to describe the strategies implementation chosen by teachers to improve the learning process effectiveness of History subject for the Tenth graders of Social Science class in MAN 1 Malang, (3) to describe the obstacles faced by teachers when the learning process takes place. The results of the study show that, (1) the strategy commonly used is the use of receptive, inquiry, jigsaw and think pair share methods (2) the process of implementing the strategies chosen by the teacher to improve the learning process effectiveness of the History subject given for Tenth graders of Social Science class in MAN 1 Malang undergo several stages. Those are the planning stage that is making lesson plans; the implementation stage, which is a preliminary stage in which the teacher checks the students’ attendance and provides stimulus to students; and the core stage where the teacher uses a variety of learning methods that have been selected such as lecture, inquiry, think pair share, and jigsaw, (3) The obstacles faced by the teacher when the learning process takes place are the students themselves. The examples are the students’ skill to comprehend the material, students’ character, some passive students and noisy students. Keywords: teacher strategy; learning effectiveness; history subject